The Roles of FOXO1 in Periodontal Homeostasis and Disease - Liang Ren; Jing Yang; Jun Wang; Xuedong Zhou; Chengcheng Liu (Journal of Immunology Research)
Periodontitis is an oral chronic inflammatory disease that is initiated by periodontal microbial communities and requires disruption of the homeostatic responses. The prevalence of periodontal disease increases with age; more than 70% of adults 65 years and older have periodontal disease. A pathogenic microbial community is required for initiating periodontal disease. Dysbiotic immune-inflammatory response and bone remodeling are characteristics of periodontitis. The transcription factor forkhead box protein O1 (FOXO1) is a key regulator of a number of cellular processes, including cell survival and differentiation, immune status, reactive oxygen species (ROS) scavenging, and apoptosis. Although accumulating evidence indicates that FOXO1 activity can be induced by periodontal pathogens, the roles of FOXO1 in periodontal homeostasis and disease have not been well documented. The present review summarizes how the FOXO1 signaling axis can regulate periodontal bacteria-epithelial interactions, immune-inflammatory response, bone remodeling, and wound healing.